Effects of diverse forage mixtures on rumen fermentation, nitrogen metabolism, and prokaryote microbial community structure in continuous culture fermenters - Jackson, Taylor; MacAdam, Jennifer; Villalba, Juan; Verma, Surbhi; Choi, Bugil; Zhai, Yuting; Jeong, KwangCheol Casey; Batistel, Fernanda (Frontiers in Animal Science, 2026)
IntroductionSeasonal declines in forage quality in crested wheatgrass-dominated rangelands of the Intermountain West reduce beef cattle performance and increase supplementation costs. Integrating legumes and forbs rich in bioactive plant secondary metabolites into pasture systems may enhance rumen fermentation and improve nutrient use efficiency. This study investigated the impact of forage mixtures on rumen fermentation, nitrogen metabolism, and the structure of prokaryotic microbial communities using a dual-flow continuous culture system.MethodsTreatments were arranged in a 5 × 5 Latin square and consisted of 1) 75% crested wheatgrass and 25% alfalfa (CW-AL), 2) 75% crested wheatgrass and 25% sainfoin (CW-SA), 3) 75% crested wheatgrass and 25% small burnet (CW-SB), 4) 75% crested wheatgrass, 12.5% sainfoin, and 12.5% small burnet, (CW-SA-SB), and 5) 75% crested wheatgrass, 8.3% sainfoin, 8.3% small burnet, and 8.3% birdsfoot trefoil (CW-SA-SB-BT).ResultsCW-AL yielded the greatest neutral detergent fiber digestibility and acetate production, significantly outperforming more diverse mixtures. Ammonia-N concentrations were highest in CW-AL and CW-SA and lowest in CW-SB. No treatment effects were observed on microbial nitrogen flow. Whereas alpha diversity was unaffected by diet, beta diversity analysis revealed differences in prokaryotic microbial community composition across treatments. Notably, the abundance of Prevotella, Succiniclasticum, and Prevotellaceae_UCG-001 was highest in CW-AL and lowest in CW-SB, whereas NK4A214_group was most abundant in CW-SB.DiscussionThese findings highlight the influence of forage diversity on rumen microbial dynamics and nutrient utilization.